One Step Biosynthesis of Gold Nanoparticles Using the Leaf Extract of Gymnema sylvestre and Study of Its In-vitro Anticancer Activity on MCF-7 Cell Lines - Sk Nurul Hasan; Koushik Paul; Aditi Dey; Subhankar Manna; Somenath Roy; Braja Gopal Bag; Sourav Mondal (International Journal of Research in Chemistry and Environment (IJRCE), 2017)
The leaf extract of Gymnema sylvestre has been utilized for the synthesis of gold nanoparticles (AuNPs) at room temperature under a very mild condition without any additional stabilizing or capping agents. Mostly spherical shaped AuNPs of 9-11 nm average diameters were obtained. The stabilized gold nanoparticles were characterized by Surface Plasmon Resonance Spectroscopy, DLS, HRTEM, Energy dispersive X-ray spectroscopy, SAED and X-Ray diffraction studies. The antioxidant activity of the leaf extract of Gymnema sylvestre has been studied against a long lived 2,2-diphenylpicrylhydrazyl (DPPH) radical at room temperature. The in-vitro MTT assay revealed a potent, selective, dose and time dependent anticancer activity of the freshly synthesized AuNPs on MCF-7 breast cancer cell lines and showed IC50 at 30.47 μg/mL.